Strengthening Public Revenue and Expenditure Management to Enhance Service Delivery - World Bank (Washington, DC, 2014)
To achieve higher growth and reduce poverty and inequality, Mexico needs to improve public service delivery. Mexico is a middle-income country with continuing high levels of poverty (46.2 percent of the population). To improve public sector service delivery, Mexico needs to ensure sufficient financial and human resources relative to the needs of the population, and effective and efficient public management of spending programs to address those needs-two basic prerequisites for an effective public sector. Mexico's public service delivery is hindered by low tax collection and expenditure inefficiencies at all three levels of government: federal, state, and municipal. Mexico's tax collection is also low by Latin American standards. The problem of low tax collection is particularly acute at the local level, as many subnational governments lack incentives and administrative capacity. At the local level, improving tax collection faces additional challenges. Low subnational tax collection increases the volatility of subnational finances within Mexico's fiscal federalism framework. Subnational governments need incentives and assistance to improve their tax administration to increase own revenues. As part of an ambitious strategy to modernize public sector financial management, the government has started to harmonize the public accounts and accounting practices of the federal and subnational governments.